Upaya Penerapan Diversi terhadap Tindak Pidana Kekerasan dengan Pelaku Anak di Polres Bima Kota - Muhammad H. A. Wahab; Juhriati; Khadijah (Jurnal Hukum Lex Generalis, 2025)
Handling violent crimes committed by children requires a special approach through a juvenile justice system that prioritizes the best interest of the child. Diversion is an alternative resolution that avoids judicial proceedings. However, in Bima City Police, its implementation has not been optimal due to structural and cultural obstacles. This study aims to analyze the application of diversion for child offenders of violence and identify its challenges and possible solutions. The research used an empirical method with primary data obtained through interviews and observations.